Kekuasaan seksualitas dalam cerpen Eka Kurniawan: Analisis Wacana Michel Foucault - Permana, Sugihartini (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2024)
This research aims to analyze the discourse of sexual power in a short story entitled Interpreter of Happiness. This research takes the form of qualitative descriptive. The object of this research is one of Eka Kurniawan's short stories in Eka Kurniawan's short story anthology book entitled